Using Animated Video to Improve Earthquake Preparedness: Evidence from a High-risk School in Padang, Indonesia - Gusrianti; Gusni Rahma (RRZ Scientific Publishing, 2025)
Elementary school students in earthquake-prone regions often lack adequate preparedness knowledge due to limited engagement with conventional learning materials. This study aimed to evaluate the effectiveness of animated videos in enhancing earthquake disaster preparedness knowledge among elementary school students. We employed a pre-experimental design with a one-group pretest–posttest approach. The study was conducted in July 2025 at SDN 23 Pasir Sebelah, Padang, selecting 50 students from grades III to V using purposive sampling. Participants received a 15-minute educational intervention that used a multisensory animated video. Students’ knowledge significantly improved following the intervention, as revealed by a paired t-test (p < 0.001). The animated video effectively communicated key concepts, including earthquake causes, early warning signs, and self-rescue techniques, resulting in a substantial increase in post-test scores compared to baseline scores. Animated video media are highly effective educational tools that align with the cognitive learning needs of elementary school students. Educational policymakers could explore integrating animated simulations into the national disaster mitigation curriculum to develop a generation that is better equipped to handle emergencies.